YOUNG CONSUMERS PREFERENCES FOR MACEDONIAN WINE - NACKA, Marina; GEORGIEV, Nenad; SIMONOVSKA, Ana (Journal Agriculture and Forestry, 2016)
Macedonian strategy for viticulture and wine production singles out young consumers as a target group of consumers for further increase of the production value and development of wine culture. Therefore, we aim to determinate the presence of young population on the Skopje Wine Winter festival in 2014 and to understand their preferences towards domestic wine and its quality. We performed structured questionnaires to 420 visitors and segmented young consumers as a focus group. We used conceptual model for analysis of consumer attitudes and Chi2-test in Stata 12.0 and StataCorp 2011, for testing the hypotheses for the consumers’ perception of quality wine. The results showed that younger consumers were the most present category on the Wine festival. In general, they do not differ from other age groups in terms of their preferences for domestic quality wine, except that this category showed readiness to pay a higher price for domestic quality wine. The quality perception of domestic wine is satisfactory, which creates an opportunity for the wineries to target and to promote their wine to the new segments of young consumers, committed to purchase domestic wine.
Keywords: young consumers’ preferences, domestic wine, quality perception.